Pengaruh Komisaris Independen, Profitabilitas dan Ukuran Perusahaan Terhadap Tax Avoidance Pada Perusahaan Consumer Non Cyclicals - Novita Wafiq Azizah (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2023)
This study examines the effects of independent commissioners, profitability, and company size on tax avoidance in consumer non-cyclical companies listed on the Indonesian Stock Exchange between 2019 and 2021. To measure tax avoidance, the study used the effective Tax Rate as the dependent variable, while independent commissioners, profitability, and company size served as independent variables. The number of the research samples taken from 22 companies obtained using by purposive sampling method. The data were analyzed using the multiple linear analysis method. The outcome demonstrates that tax avoidance is negatively impacted by company size, profitability, and independent commissioners.